Dipturus nidarosiensis ... - Ebert, David A.; Wintner, Sabine P.; Kyne, Peter M. (Zenodo, 2021)
Dipturus nidarosiensis (Storm, 1881) Norwegian Skate Raja nidarosiensis Storm, (ex Collett) 1881: 80. Syntypes: ZMUO J6339 (1 stuffed in poor condition), ZMUO (2, lost). Type locality: Munkholmen, Trondheim Fjord, Norway. Local synonymy : Raja ( Dipturus ) springeri : Compagno et al ., 1989: 92, pl. (in part); Compagno et al ., 1991: 96 (in part). Dipturus springeri : Compagno, 1999: 116 (in part); Compagno & Ebert, 2007: 139, fig. 6e (in part); Ebert et al ., 2008: 88 (in part); NPOA, 2013: 56 (in part); da Silva et al ., 2015: 247 (in part); Ebert, 2015: 176, fig. 195 (in part?); Ebert & van Hees, 2015: 147 (in part). Dipturus nidarosiensis : Ebert & Compagno, 2007: 119; Last et al ., 2016f: 21; Last et al ., 2016g: 266, fig. 19.57. South Africa voucher material : Uncertain, all previous large Dipturus species off the west and south coasts of South Africa have been referred to as D. springeri . The specimens listed here were all from the west and south coasts of South Africa and may be D. ... : Published as part of Ebert, David A., Wintner, Sabine P. & Kyne, Peter M., 2021, An annotated checklist of the chondrichthyans of South Africa, pp. 1-127 in Zootaxa 4947 (1) on page 80, DOI: 10.11646/zootaxa.4947.1.1, http://zenodo.org/record/4614567 ...